Rational design of artificial dye-decolorizing peroxidases using myoglobin by engineering Tyr/Trp in the heme center. Issue 34 (10th August 2017) - Li, Le-Le; Yuan, Hong; Liao, Fei; He, Bo; Gao, Shu-Qin; Wen, Ge-Bo; Tan, Xiangshi; Lin, Ying-Wu
Abstract : Artificial dye-decolorizing peroxidases (DyPs) have been rationally designed using myoglobin (Mb) as a protein scaffold by engineering Tyr/Trp in the heme center, such as F43Y/F138 W Mb, which exhibited catalytic performance comparable to some native DyPs. Abstract : The rational design of metalloenzymes provides advantages not only for illustrating the structure and function relationship of native enzymes, but also for creating functional artificial enzymes comparable to native enzymes. Dye-decolorizing peroxidases (DyPs) are a new family of heme peroxidases and have received much attention recently. Inspired by the structural features of native DyPs with multiple Tyr and Trp residues, we herein aimed to design functional artificial DyPs using myoglobin (Mb), an O2 carrier as a protein scaffold, by further introduction of Tyr/Trp into the secondary sphere of the heme center in the F43Y Mb mutant. The latter has been shown to possess a novel Tyr–heme cross-link and exhibit enhanced peroxidase activity, which provides an ideal platform to design a series of derivatives, including F43Y/F46Y Mb, F43Y/I107Y Mb, F43Y/F138 W Mb and F43Y/I107Y/F138 W Mb. Our design revealed that the Tyr–heme cross-link was well-retained in the mutants except for F43Y/F46Y Mb, as confirmed by X-ray crystal structure analysis. More importantly, stopped-flow kinetic studies showed that these derivatives exhibit enhanced dye-decolorizing peroxidase activities compared to that of wild-type (WT) Mb. This is particularly the case for the double mutant F43Y/F138 W Mb, exhibiting an overall catalytic efficiency ( k cat / K m ) of 110 670 M −1 s −1, which is ∼144-fold and ∼20-fold that of WT Mb and F43Y Mb, respectively, and is ∼4.3-fold that of native DyP from Vibrio cholerae . Stopped-flow, electron paramagnetic resonance (EPR) and isothermal titration calorimetry (ITC) studies further provided insights into the activation of H2 O2 and the binding of a substrate, reactive blue 19 (RB19), to the double mutant. This study provides valuable information for elucidating the structure and dye-decolorizing function relationship of peroxidases, and also clues for the design of other functional artificial heme enzymes.